Anxiety disorders in acute central nervous system infections - Elena Bozzola; Giulia Spina; Paola Bergonzini; Mauro Bozzola; Massimiliano Raponi; Alberto Villani (BMC, 2020)
Abstract Background Patients affected by acute central nervous system (ACNS) infectionsmay present different complications, including neuropsychological disorders. Nevertheless, psychopathological impairment has been rarely measured by appropriate and validated tests. Material and methods Survivors of childhood ACNS infections admitted to the Bambino Gesù Children's Hospital, Rome, Italy, from June 2013 to June 2015 were re-evaluated at follow-up from June 2016 to June 2017. Both patients and their parents underwent a psychological interview and neuropsychological tests (the Leiter International Performance Scale - revised (Leiter-R), the Child Behaviour Checklist (CBCL), the K-SADS-PL test). Results Thirty children were included in the study. The mean score of IQ and fluid reasoning was within the normal range. A percentage of 20% of the children enrolled showed criteria for generalized anxiety disorder. Conclusion Our study revealed the importance of follow-up evaluations after ACNS infections, in order to prevent mayor psychological sequelae and to perform treatment or rehabilitation.